Lipid Biosynthesis and Protein Concentration Respond Uniquely to Phosphate Supply during Leaf Development in Highly Phosphorus-Efficient Hakea prostrata . Issue 4 (14th October 2014) - Kuppusamy, Thirumurugen; Giavalisco, Patrick; Arvidsson, Samuel; Sulpice, Ronan; Stitt, Mark; Finnegan, Patrick M.; Scheible, Wolf-Rüdiger; Lambers, Hans; Jost, Ricarda
Abstract : The Australian Proteaceae Hakea prostrata transcriptionally regulates only a small number of genes to generate polar leaf lipid profiles associated with delayed greening and efficient phosphorus use . Abstract: Hakea prostrata (Proteaceae) is adapted to severely phosphorus-impoverished soils and extensively replaces phospholipids during leaf development. We investigated how polar lipid profiles change during leaf development and in response to external phosphate supply. Leaf size was unaffected by a moderate increase in phosphate supply. However, leaf protein concentration increased by more than 2-fold in young and mature leaves, indicating that phosphate stimulates protein synthesis. Orthologs of known lipid-remodeling genes in Arabidopsis ( Arabidopsis thaliana ) were identified in the H. prostrata transcriptome. Their transcript profiles in young and mature leaves were analyzed in response to phosphate supply alongside changes in polar lipid fractions. In young leaves of phosphate-limited plants, phosphatidylcholine/phosphatidylethanolamine and associated transcript levels were higher, while phosphatidylglycerol and sulfolipid levels were lower than in mature leaves, consistent with low photosynthetic rates and delayed chloroplast development. Phosphate reduced galactolipid and increased phospholipid concentrations in mature leaves, with concomitant changes in the expression of only four H. prostrata genes, GLYCEROPHOSPHODIESTER PHOSPHODIESTERASE1, N-METHYLTRANSFERASE2, NONSPECIFIC PHOSPHOLIPASE C4, and MONOGALACTOSYLDIACYLGLYCEROL3 . Remarkably, phosphatidylglycerol levels decreased with increasing phosphate supply and were associated with lower photosynthetic rates. Levels of polar lipids with highly unsaturated 32:x (x = number of double bonds in hydrocarbon chain) and 34:x acyl chains increased. We conclude that a regulatory network with a small number of central hubs underpins extensive phospholipid replacement during leaf development in H. prostrata . This hard-wired regulatory framework allows increased photosynthetic phosphorus use efficiency and growth in a low-phosphate environment. This may have rendered H. prostrata lipid metabolism unable to adjust to higher internal phosphate concentrations.